Prostitution in Malawi and the HIV/AIDS Risk (Nordic Journal of African Studies, 2000)
Prostitution is not always easy to define, especially on a cross-cultural basis. In the African context, there can be a continuum between offering gifts for sexual services and more commercially-oriented sex work. It can form an element of a cash nexus between men and women, in a situation where those absorbed into wage labour have been overwhelmingly male. A study of gossip and off-the cuff remarks concerning prostitution in the Zomba district, Malawi, is reported. A link between geographical movement by wealthier males and casual sexual activity is observed, with payment a form of distribution of largesse. Commercial prostitutes (‘bar girls’) were seen also to recognise the risk, but were found to feel there was no alternative, that they had AIDS anyway, or that mortality was decided simply by fate. Some clients used condoms but others refused, and even some prostitutes would not use them. Explanation of prostitutes’ behaviour can be seen as mainly economic, but considerable male patronage despite known risks needs also to be recognised.